A multidisciplinary dermatology-gastroenterology-rheumatology (DER.RE.GA) unit for the care of patients with immune-mediated inflammatory diseases: analysis of the first 5 years from the dermatologist’s perspective - Brazzelli, Valeria; Bobbio Pallavicini, Francesca; Maggi, Paolo; Chętko, Łukasz; Isoletta, Eugenio; Di Giuli, Nicolò; Bonelli, Alice; Fornaroli, Valentina (Frontiers in Medicine, 2023)
Immune-mediated inflammatory diseases (IMIDs) constitute a heterogenous group of chronic and highly disabling conditions. The clinical challenges they often pose led to formation of numerous dermo-rheumatological interdisciplinary units around the world, which are reported to benefit their patients in various ways. The present paper describes our experience with a multidisciplinary dermatology-rheumatology-gastroenterology unit DERREGA at the IRCCS Foundation Policlinico San Matteo of Pavia over a period of 5 years of its activity (2017–2022). A digital database was created, containing the medical records of 146 patients referred to the dermatology unit only by rheumatologists or gastroenterologists belonging to the multidisciplinary unit DERREGA. Then, aspects such as demographics, initial basis of referral and final diagnosis among the patients were analyzed retrospectively. Patients were classified as either gastroenterological or rheumatological, and then categorized according to the specific basis of referral. Most of the gastroenterological patients (97%) were affected by inflammatory bowel diseases (IBDs). Rheumatological patients were divided in three subgroups, including patients referred with vasculitis, arthropathies (undifferentiated arthritis, psoriatic arthritis and other arthritis) and other rheumatological diseases. Then, final diagnoses were evaluated in each group. Almost a third of IBD patients received a diagnosis of paradoxical psoriasis. Dermatological examination allowed diagnosis of minimal psoriasis based on Caspar criteria in over 70% of the patients admitted with undifferentiated arthritis. A multidisciplinary approach is suggested to provide more effective management of IMIDs and, specifically, from a dermatological perspective, allows for the diagnosis of minimal manifestations of psoriasis in patients with a provisional diagnosis of undifferentiated arthritis.